The Simulation and Experiment of a Non-Cross-Feeding Printed Log-Periodic Antenna - Chun-Ying Kang; Shu Lin; Zhi-Hua Zhao; Li-Wen Jing (International Journal of Antennas and Propagation)
A non-cross-fed printed log-periodic antenna is simulated and studied experimentally. To avoid complex feeding with long coaxial line, the non-cross-feeding structure is applied in this antenna. The software CST Microwave Studio is employed to simulate the proposed antenna, and the optimized antenna model is obtained. According to the simulation results, the antenna prototype is produced and measured. Simulation and measured results show that the antenna is with S11<-10 dB in band of 4.2–9.2 GHz. And the radiation pattern and gain vary steadily in this band, which achieves requirements for wideband antenna. This antenna design can be extended to the design of the antenna integrated in communication circuit.